The 40-year history of modeling active dendrites in cerebellar Purkinje cells: emergence of the first single cell “community model” - Bower, James M. (Frontiers in Computational Neuroscience, 2015)
The subject of the effects of the active properties of the Purkinje cell dendrite on neuronal function has been an active subject of study for more than 40 years. Somewhat unusually, some of these investigations, from the outset have involved an interacting combination of experimental and model-based techniques. This paper recounts that 40-year history, and the view of the functional significance of the active properties of the Purkinje cell dendrite that has emerged. It specifically considers the emergence from these efforts of what is arguably the first single cell ‘community’ model in neuroscience. The paper also considers the implications of the development of this model for future studies of the complex properties of neuronal dendrites.